Pernicious Martial Law Imprints Still Palpable - Ocampo, Satur (Social Sciences and Development Review, 2012)
The article highlights the premise that human rights violations and martial law abuses are still at the fore in today’s context. The author, a political prisoner during martial law regime, and a victim of torture himself, provides somewhat an insider’s account and discusses impunity as one of the reasons why there is still markings and shadow military rule, also why such conditions prevailed up to now, and as well as why military police abuses have not been stopped despite the new administrations effort.